Mapping deterioration in electrospun zein nonwoven nanostructures encapsulating corn oil - Louis A. Colaruotolo; Singam Suranjoy Singh; Stacie Dobson; Loong-Tak Lim; Iris J. Joye; Michael A. Rogers; Maria G. Corradini (Current Research in Food Science)
Electrospun nonwovens of biopolymers are gaining popularity in filtration, coatings, encapsulation, and packaging materials. However, their applications are hindered by limited stability, particularly when loaded with lipids. This research aimed to apply a multiscale approach to gain insights into deteriorative processes, e.g., oxidation, limiting the shelf life of these complex materials, using corn oil-loaded electrospun zein nonwovens as a model system. Oil-doped zein electrospun nonwovens were stored in the dark at 23 °C and 33% relative humidity for 28 days and tested at selected intervals to monitor their morphology and mechanical properties. Lipid oxidation was assessed using the thiobarbituric acid reactive species (TBARS) assay. The photophysical properties of intrinsic, i.e., tyrosine (Tyr), and extrinsic, i.e., boron-dipyrromethene undecanoic acid 581/591 (BODIPY C11), lumiphores were also monitored to evaluate changes in local molecular rigidity, and oxidation, respectively. The protein secondary structure was determined with Fourier transform infrared spectroscopy (FTIR). Scanning electron microscopy (SEM) analysis of the oil-loaded electrospun nonwovens revealed that the diameter of the ribbon-like fiber significantly decreased during storage from 701 ± 23 nm to 620 ± 44 nm. Breakage of the electrospun fibers was observed and correlated with increased brittleness and molecular rigidity of the nonwoven material, reflected by an increase in Tyr emission intensity and phosphorescence lifetime. Changes in tensile strength, brittleness and matrix rigidity also correlated with a zein secondary structure transition from unordered to ordered β-sheets. Raman and luminescence micrographs showed oil migration during storage, thereby increasing lipid oxidation. The correlation between local rigidity and lipid distribution/oxidation suggests that reorganizing protein structures increased material brittleness and displaced encapsulated oils within the electrospun fiber. Understanding deteriorative mechanisms aids in developing innovative strategies to improve the stability of these novel food-grade materials.